Sembilan Matahari’s Vmaps: Retelling Geographical Memories and Narratives in Digital Culture - Allo, Katherina (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2015)
Images and representations have long been used to tell the history of a place, to crystalize local memories, myths and beliefs, and to share meaningful values in a collective life. Sembilan Matahari, one of the nationally renown film-makers and video artists in Indonesia, has produced works of video-mapping (vmap) from 2010 to 2014 in public spaces as part of the local events to celebrate and re-activate the life of a people. Through Sembilan Matahari’s works the city of Jakarta, Pekalongan and Bandung have animated their iconic buildings to tell their stories and renew the memories of the place and the people. This article is based on a research examining the spatial construction of the event and the video-mapping, and how these spatial constructions relate to the geographical memories and narratives of the place. By using phenomenological approaches, this writing will explain how the three spatial constructions relate to one another, and how the reading/ interpretation of the video-mapping occur in experiencing Sembilan Matahari’s works.